Slovensko morsko ribištvo v svojem izginjanju - Požar, Luka (Geografski obzornik, 2023)
The geographical characteristics of the Gulf of Trieste are extremely important for the development of the fishing industry in the area, because they affect the formation of specific starting conditions for the development of this economic activity. In recent times, its importance has been declining considerably, which is also evidenced by statistical data about marine industrial fishing. Fishing has slowly been abandoned or turned into a complementary activity. Namely, many fishermen engage in tourist activities during the summer. To preserve the fishing industry the European Union provides financial support and assistance.
Keywords: economic geography; ekonomska geografija; fishing; fishing industry; Gulf of Trieste; maritime geography; pomorska geografija; ribištvo; ribolov; Slovenia; Slovenija; Slovenska Istra; Tržaški zaliv